Wear of Stellite 6 Coatings Produced with High-Velocity Oxygen Fuel at Elevated Temperatures - Alejandra Islas Encalada; Pantcho Stoyanov; Mary Makowiec; Christian Moreau; Richard R. Chromik (Lubricants, 2025)
This paper investigates the tribological behavior of Stellite 6 coatings produced with high-velocity oxygen fuel (HVOF), with an emphasis on the transition between severe and mild wear regimes and the glaze layer formation. The development of these coatings involved two spray parameters modifying the oxygen fuel ratio and three post-heat treatment conditions at temperatures ranging between 600 °C and 1150 °C. The coatings were tested under conditions varying the normal load, temperature, sliding distance, and testing temperatures (up to 300 °C). The results show that the coating obtained from the HVOF process exhibited a microstructure different from the conventional bulk Co-alloys, significantly impacting the wear performance. The coating post-processing was essentialto enhance wear resistance at elevated temperatures.